Choosing EMI Schools: A Case Study of Parental Decisions and Shifting Language Ideologies in Indonesia - Maharani, Anisa Frisca; Nurkamto, Joko; Adi Putra, Kristian (Universitas Hamzanwadi, 2024)
The rise of English as a Medium of Instruction (EMI) schools reflects a global trend driven by the increasing demand for English proficiency in non-native English-speaking countries. This study investigates the factors driving Indonesian parents’ decisions to enrol their children in English Medium Instruction (EMI) schools, focusing on the interplay of socioeconomic status, shifting language ideologies, and cultural preservation. Employing a qualitative case study approach, the research captures the nuanced motivations of parents from diverse socioeconomic backgrounds, uncovering how aspirations for global success and fears of cultural erosion shape educational choices. The findings reveal that parents of high socioeconomic status view EMI schools as strategic investments for international opportunities, while lower socioeconomic groups balance affordability with a commitment to cultural identity. Shifting language ideologies highlight the prioritization of English as a global asset, often at the expense of local languages, generating tensions between economic aspirations and cultural preservation. These insights underline the urgent need for policies integrating multilingual education, equitable access to EMI schools, and promoting linguistic diversity. This study contributes to the discourse on globalization, education, and cultural sustainability in multilingual contexts by addressing these dynamics.